Effect of Sluice Gate Opening Height on Spillway on Flow Characteristics (Physical Model) - Adianti, Feni; Priyambodho, Bambang Adhi; Wigati, Restu; Purnaditya, Ngakan Putu; Subekti, Subekti (JURUSAN TEKNIK SIPIL, 2024)
The sluice gate is a measuring structure that controls the upstream discharge and water level. The varying height of the sluice gate opening will cause the water level to vary both upstream and downstream. The difference in water level upstream and downstream can potentially cause scouring downstream of the gate. This study aimed to determine the effect of the height of the sluice gate opening on the flow characteristics. This study used a research method in the form of a physical model on an open channel (flume) at the Integrated Laboratory of Sultan Ageng Tirtayasa University Sindangsari. The stages of this research included pitot pipe calibration and research of flow characteristics on the height of the gate opening with variations in the height of the sluice opening (9, 10, 11, 12, 13 cm). The sluice model used is made of wooden boards with the dimensions of the door width being 1/3 of the width of the channel. The results showed that the higher the sluice opening (a), the lower the upstream water level (H) and the greater the downstream water level (Y). While the upstream flow velocity (V0) was greater and the downstream flow velocity (V1) was getting smaller so were the upstream Froude numbers (Frupstream) and downstream Froude numbers (Frdownstream). The upstream flow is classified as sub-critical flow (Fr<1), while the downstream flow is classified as super-critical flow (Fr>1).